2022
DOI: 10.1093/oep/gpac040
|View full text |Cite
|
Sign up to set email alerts
|

A year of COVID: the evolution of labour market and financial inequalities through the crisis

Abstract: We use high-quality UK panel data to document the extent that pre-existing labour market and financial inequalities were exacerbated by the pandemic between April 2020 and September 2021. Some inequalities worsened, others did not, and in some cases, initial widening of labour market inequalities was subsequently reversed. We find no evidence of an overall divergence in labour market outcomes by gender. Initial changes for ethnic minorities and the young were largely reversed by March 2021. Those in the top th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…This pattern would imply greater increases in savings for higher-income households than for lower-income households. Crossley et al (2021) corroborate this, finding that unprecedented increases in household savings took place during the pandemic, and that the resulting increase in net wealth was higher for higher-income households. Figure 2.4 shows evidence from the Understanding Society COVID-19 study: the yellow line, which represents the percentage of respondents in each longrun income decile who reported having experienced a rise in net wealth of more than 10%, is higher than the green line, the percentage who reported having seen a fall of more than 10%, in all except the bottom two income deciles.…”
Section: Changes In the Prevalence Of Low Financial Wealth Over Timesupporting
confidence: 62%
See 1 more Smart Citation
“…This pattern would imply greater increases in savings for higher-income households than for lower-income households. Crossley et al (2021) corroborate this, finding that unprecedented increases in household savings took place during the pandemic, and that the resulting increase in net wealth was higher for higher-income households. Figure 2.4 shows evidence from the Understanding Society COVID-19 study: the yellow line, which represents the percentage of respondents in each longrun income decile who reported having experienced a rise in net wealth of more than 10%, is higher than the green line, the percentage who reported having seen a fall of more than 10%, in all except the bottom two income deciles.…”
Section: Changes In the Prevalence Of Low Financial Wealth Over Timesupporting
confidence: 62%
“…Of course, this cannot necessarily be interpreted as a causal effect of financial wealth, as those with low savings may have other characteristics associated with greater vulnerability to economic shocks. For example, Crossley et al (2021) found that those with low pre-COVID household incomes were also more likely to fall into arrears on bills. In Section 3.4, we will offer evidence that this is indeed a causal relationship.…”
Section: Prevalence Of Financial Difficultiesmentioning
confidence: 99%
“…Like the rotating modules, special one-off studies, such as the COVID-19 study, can open up new avenues for economic research. Crossley, Fisher and Low (2021) and Crossley et al (2023) used data from the COVID-19 study to characterise the prevalence of economic hardship across different groups and through the course of the pandemic. Etheridge et al (2023) explored the link between workat-home productivity, job characteristics and individual traits.…”
Section: Rich Economic Contentmentioning
confidence: 99%
“…Crossley, Fisher and Low (2021) and Crossley et al. (2023) used data from the COVID‐19 study to characterise the prevalence of economic hardship across different groups and through the course of the pandemic. Etheridge et al.…”
Section: Strengths and Opportunities For Research In Economics And Po...mentioning
confidence: 99%